AMONG THE MULBERRY VARIETIES IN THE "WORLD MULBERRY COLLECTION" OF SELECTED JARARIQ-1 AND JARARIQ-4 VARIETIES ECONOMIC INDICATORS (British Journal of Global Ecology and Sustainable Development, 2026)
This article presents information about frost- and disease-resistant, high-yielding mulberry varieties Zhararik-1 and Zhararik-4 from the "World Mulberry Collection" created by scientists at the Research Institute of Sericulture.